A comparison of the evaluation of teacher candidates’ views on culture-meaning relationship between the years of 2005-2015 - (:unkn) unknown (Sakarya University, 2016)
Culture is the body of values which defines and interprets the society it belongs and the life of this society. Culture is a human-specific term which formed by abstract and rational thinking ability. These abstract values become concrete on objects of life. Culture has an alive, self-feeding and regenerative organism, which is dynamic and has its own inner dynamics. Thus, culture has to improve and change. The purpose of this study is to compare the results of a previous study done in 2005 with the same study done in 2015 which involves the evaluation of the thoughts of teacher candidates on the meanings carried by the word “culture”. The pattern of this study is determined to be qualitative research method. Data is gathered in the lecture of visual arts for preschool teaching in the 2014-2015 school year. The teacher candidates are asked for the meanings carried by the culture concept and the data gathered is interpreted by descriptive analysis. The results are compared with the results of the same study done in 2005. © The Turkish Online Journal of Educational Technology.